2019
DOI: 10.1016/j.plantsci.2018.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Mini review: Revisiting mobile RNA silencing in plants

Abstract: Non-cell autonomous RNA silencing can spread from cell to cell and over long-distances in animals and plants. This process is genetically determined and requires mobile RNA signals. Genetic requirement and molecular nature of the mobile signals for non-cell-autonomous RNA silencing were intensively investigated in past few decades. No consensus dogma for mobile silencing can be reached in plants, yet published data are sometimes inconsistent and controversial. Thus, the genetic requirements and molecular signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a distinct class of endogenous, noncoding small RNAs that play a very important role in posttranscriptional gene regulation via the degradation of target mRNAs or the repression of targeted gene translation (Voinnet 2009). Increasing evidence shows that miRNAs are vital components of the posttranscriptional regulation of gene expression, which is important for almost all aspects of plant biological development, such as tissue differentiation, signal transduction, growth phase switching, and response to stresses (Vance and Vaucheret 2001;Baulcombe 2004;Millar and Gubler 2005;Xie and Qi 2008;Li et al 2011;Soitamo et al 2012;Yang et al 2013a, b, c;Cui et al 2014;Kontra et al 2016;Liu and Chen 2016;Adkar-Purushothama et al 2018;Li and Wang 2018;Zhang et al 2018Zhang et al ,2019Sun Sparks et al 2019). Recently, with the rapid development of high-throughput sequencing technology, several studies have identified miRNAs and their target genes on a genomewide level in crops during anther development (Chambers and Shuai 2009;Wei et al 2013a, b;Yang et al 2013aYang et al , b, c, 2016Jiang et al 2014;Zhang et al 2016Zhang et al ,2018.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a distinct class of endogenous, noncoding small RNAs that play a very important role in posttranscriptional gene regulation via the degradation of target mRNAs or the repression of targeted gene translation (Voinnet 2009). Increasing evidence shows that miRNAs are vital components of the posttranscriptional regulation of gene expression, which is important for almost all aspects of plant biological development, such as tissue differentiation, signal transduction, growth phase switching, and response to stresses (Vance and Vaucheret 2001;Baulcombe 2004;Millar and Gubler 2005;Xie and Qi 2008;Li et al 2011;Soitamo et al 2012;Yang et al 2013a, b, c;Cui et al 2014;Kontra et al 2016;Liu and Chen 2016;Adkar-Purushothama et al 2018;Li and Wang 2018;Zhang et al 2018Zhang et al ,2019Sun Sparks et al 2019). Recently, with the rapid development of high-throughput sequencing technology, several studies have identified miRNAs and their target genes on a genomewide level in crops during anther development (Chambers and Shuai 2009;Wei et al 2013a, b;Yang et al 2013aYang et al , b, c, 2016Jiang et al 2014;Zhang et al 2016Zhang et al ,2018.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…This phenomenon has been observed in multiple species using grafting of genotypes containing silencing transgenes, by initiation of local silencing using Agrobacterium infiltration of hairpin constructs, by expression of hairpins or amiRNAs under control of tissue specific promoters, or by topical introduction of a dsRNA (Palauqui et al 1997;Voinnet and Baulcombe 1997;McHale et al 2013;Dalakouras et al 2016). The signal for systemic silencing has not been conclusively determined but is generally thought to be an RNA (Melnyk et al 2011;Taochy et al 2017;Zhang et al 2019). sRNAs can move from cell-to-cell in plants through plasmodesmata or longer distances through vascular tissues (Melnyk et al 2011;Liu and Chen 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To support or refute our hypothesis about silencing-mediated resistance to PPV infection, we expanded our expertise in an open challenge to engineer amiRNA in plants and verify the potential ability of amiRNA to protect plants [11][12][13][14][15][16]19,21]. The idea to combine ami-siRNA into a gene construct came from the natural contribution of each RNAi molecule for the transcriptional and posttranscriptional control of mRNA in eukaryotes [32][33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%